Discussão sobre a viabilidade de exploração de gás em folhelho na Bacia do Amazonas - CARDOSO, Gabriel Lobato (2021)
This work synthesizes the fundamental concepts involved in a possible shale gas exploration in the Amazonas basin, approaching them in an interdisciplinary way from the correlation of geophysical, geological, economic and environmental aspects. This approach was the base for the presentation of geophysical and geochemical data to the delimitation of potential shale gas regions and subsequent discussions. There were bibliographic reviews of monographs, dissertations, theses, books, class notes, websites, presentations, seminars, event proceedings, roundtables, institutional reports and national and international articles. The data presented correspond to previous academic works and the public data given by the Agência Nacional do Petróleo, Gás Natural e Biocombustíveis (ANP) and by private companies. The analysis of the available data led to the delimitation of the region around the Tapajós River, in the state of Pará, as a potential zone for shale gas generation and accumulation. Given its degree of maturity, when compared to other regions of the basin previous exploration, which indicated characteristics similar to those ones found in other shale gas sites and their recorded fracture intervals. The text shows a discussion about the feasibility of such exploration for the Amazon Region, taking into consideration its reality concerned the development of consumer markets, gas transportation networks, the application of hydraulic fracturing and the environmental aspects are considered and also the application of microseismic for fracture propagation monitoring and current legislation. The feasibility discussion indicated that the Carajás Mining Complex is the main consumer market for shale gas supplying, given the energy intensive role of its mining activities being near target zone. The pipelines stood out as supplying options due the analysis of the political and socio-environmental reality of the Amazon Region. Lastly, SWOT analysis discuss the implications of Brazilian Law concerned to shale gas.